Práticas e representações nos primeiros anos do Gabinete de Leitura de Jundiaí (1908-1924) - Oliveira, Paulo Henrique de (2015)
The research aims to understand the process of emergence of Jundiaí Reading Room. Founded in 1908, in Jundiaí, located in the western region of São Paulo. The institution was created by a group of workers of Railroads of Companhia Paulista. It was intended to be a space for education, fostering a bookish sociability, through literary conferences and ceremonies and a school of first letters to members and patrons. It was configured as a space dedicated to books, readers and practice of reading, the first public library in the city of Jundiaí. From Meeting Minutes, produced between 1908-1924, analyzes the social practices of officials, who gathered in General Meetings or Board meetings. Investigates the representation of the institution as a space for the practice of literacy. Therefore, we used the ideas formulated by Roger Chartier, practices and representations in an attempt to understand how a social reality was being built, and thought given to read, by the founders and members of the Reading Room, understanding that practices build representations the social world. The survey also looks at the Library of Jundiaí Reading Room. In 1957, the librarian of the institution produced a catalog of works containing 9.027 books described (between domestic and foreign works), listing them only by title and author. The catalog covers all the works that made up the collection of the institution since its foundation. Thus, there were the classification and sorting of the articles from the Dewey Decimal Classification, in order to identify to the literary preferences, once the books were purchased according to the choices of the readers being able to so get an overview of the major literary genres. Finally, it appears that the time and the space, marking the emergence of Jundiaí Reading Room are revealing a period of transformation, in which new social arrangements were experienced in the First Republic order